(untitled) (Agricultural Engineering, 2018)
The paper presents analysis of efficiency of the logging unit comprising Belarus 820 farm tractor and PD80 logging trailer equipped with Ryś-1 crane. Analysis was made based on the working day timing. The unit logged 1- meter long tree pieces (hornbeam, oak, birch) from the area where material for logging was distributed irregularly on the entire felling site. Unfavourable atmospheric conditions were reported during the working day (a thick layer of snow, low temperature, not frozen soil) which could have influenced the unit operation performance. Despite that the performance of the logging unit was comparable to similar logging units described in the literature. Determined coefficient of use of the operating time of the machine K02 was 0.93, coefficient of use of the shift working time K04 − 0.9, coefficient of use of the shift exploitation time K07 − 0.8. Hourly performance in the shift exploitation time was 4.98 m3·h−1, efficiency in the shift working time W02 − 4.80 m3·h−1 and performance in the general shift time W07 − 4.30 m3·h−1.